Investigations of LHW-plasma coupling and current drive at high density related to H-mode experiments in EAST. (21st August 2015) - Ding, B.J.; Li, Y.C.; Zhang, L.; Li, M.H.; Wei, W.; Kong, E.H.; Wang, M.; Xu, H.D.; Wang, S.L.; Xu, G.S.; Zhao, L.M.; Hu, H.C.; et al.
Abstract: Two important issues in achieving lower hybrid current drive (LHCD) high confinement plasma in EAST are to improve lower hybrid wave (LHW)-plasma coupling and to drive the plasma current at a high density. Studies in different configurations with different directions of toroidal magnetic field ( B t ) show that the density near the antenna is affected by both the radial electric field induced by plasma without a LHW ( E r_plasma ) in the scrape off layer (SOL), and the radial electric field induced by LHW power ( E r_LH ) near the grill. Investigations indicate thatE r × B t in the SOL leads to a different effect of configuration on the LHW-plasma coupling andE r_LH × B t accounts for the asymmetric density behaviour in the SOL observed in the experiments, where E r is the total radial electric field in the SOL. Modelling of parametric instability (PI), collisional absorption (CA) and scattering from density fluctuations (SDF) in the edge region, performed considering the parameters of high density LHCD experiments in EAST, has shown that these mechanisms could be responsible for the low current drive (CD) efficiency at high density. Radiofrequency probe spectra, useful for documenting PI occurrence, show sidebands whose amplitude in the case of the lithiated vacuum chamber is smaller than in the case of poor lithiation, consistently with growth rates from PI modeling of the respective reference discharges. Since strong lithiation is also expected to diminish the parasitic effect on the LHCD of the remaining possible mechanisms, this appears to be a useful method for improving LHCD efficiency at a high density.